In situ gelling hydrogel loaded with berberine liposome for the treatment of biofilm-infected wounds - Li, Sipan; Wang, Yongan; Wang, Siting; Xie, Jianjun; Fu, Tingming; Li, Shaoguang (Frontiers in Bioengineering and Biotechnology, 2023)
Background: In recent years, the impact of bacterial biofilms on traumatic wounds and the means to combat them have become a major research topic in the field of medicine. The eradication of biofilms formed by bacterial infections in wounds has always been a huge challenge. Herein, we developed a hydrogel with the active ingredient berberine hydrochloride liposomes to disrupt the biofilm and thereby accelerate the healing of infected wounds in mice. Methods: We determined the ability of berberine hydrochloride liposomes to eradicate the biofilm by means of studies such as crystalline violet staining, measuring the inhibition circle, and dilution coating plate method. Encouraged by the in vitro efficacy, we chose to coat the berberine hydrochloride liposomes on the Poloxam range of in-situ thermosensitive hydrogels to allow fuller contact with the wound surface and sustained efficacy. Eventually, relevant pathological and immunological analyses were carried out on wound tissue from mice treated for 14 days. Results: The final results show that the number of wound tissue biofilms decreases abruptly after treatment and that the various inflammatory factors in them are significantly reduced within a short period. In the meantime, the number of collagen fibers in the treated wound tissue, as well as the proteins involved in healing in the wound tissue, showed significant differences compared to the model group. Conclusions: From the results, we found that berberine liposome gel can accelerate wound healing in Staphylococcus aureus infections by inhibiting the inflammatory response and promoting re-epithelialization as well as vascular regeneration. Our work exemplifies the efficacy of liposomal isolation of toxins. This innovative antimicrobial strategy opens up new perspectives for tackling drug resistance and fighting wound infections.